The Effect of Role Conflict and Locus of Control to The Organizational Culture - Hartono; Fachrudy Asj’ari; Moch. Afrizal M (Enrichment : Journal of Management, 2022)
This study would like to asses the role conflict and locus of control which have to be performed by PT. Shabilla Eraldo Utama in Sidoarjo in connection with organizational culture of the employees. This research was conducted at PT. Shabilla Eraldo Utama employee in Sidoarjo which covered 50 employees as respondent. This research utilize regression, the technique was processed with SPSS program 21.0 to analyze some hypothesis. The study uses saturated sampling techniques or commonly called census. Data analysis techniques using Multiple Linear Regression. The correlations models between these variables in this research explain that three hypothesis have significant correlation. The results of the data analysis showed that role conflict has a significant and positive effect on the culture of employee organization. Locus of control has a significant and positive impact on the culture of employee organizations. Role Conflict and Locus of Control have a significant and positive effect on the culture of employee organization. The result of this research were empirical date of the development of the theoretical of human resources and practice management.